Haslea sigma (Naviculaceae, Bacillariophyta) a new sigmoid benthic species from salt marshes of Southern Brazil - Talgatti, Dávia; Sar, Eugenia; Torgan, Lezilda Carvalho (Phytotaxa, 2014)
A new sigmoid diatom species Haslea sigma sp. nov. was found alive in sediment composed of clay and silt in salt marshes in Southern Brazil. The species is morphologically distinctive by the following combination of characters: 1) sigmoid valve, 2) thickened virgae forming a pseudostauros, 3) central raphe fissures almost straight and 4) terminal raphe fissures slightly curved. It was analyzed in light and electron microscopy and compared with the sigmoid Haslea nipkowii and with other spindle-shaped Haslea taxa possessing a pseudostauros.